2022
DOI: 10.3390/fi14110302
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Sensitive Data in the Information Age: State of the Art and Future Prospects

Abstract: The present information age is characterized by an ever-increasing digitalization. Smart devices quantify our entire lives. These collected data provide the foundation for data-driven services called smart services. They are able to adapt to a given context and thus tailor their functionalities to the user’s needs. It is therefore not surprising that their main resource, namely data, is nowadays a valuable commodity that can also be traded. However, this trend does not only have positive sides, as the gathered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 199 publications
0
5
0
Order By: Relevance
“…The intersection of artificial intelligence (AI) and machine learning (ML) with healthcare privacy has led to significant advancements in protecting sensitive patient information. Some studies revealed how AI algorithms could be trained to automatically redact sensitive information from healthcare records, thereby reducing the risk of data exposure [21], [22]. ML models could effectively classify data access as either legitimate or suspicious, thus streamlining the audit process [23], [24].…”
Section: B Ai/ml In Enhancing Healthcare Privacymentioning
confidence: 99%
“…The intersection of artificial intelligence (AI) and machine learning (ML) with healthcare privacy has led to significant advancements in protecting sensitive patient information. Some studies revealed how AI algorithms could be trained to automatically redact sensitive information from healthcare records, thereby reducing the risk of data exposure [21], [22]. ML models could effectively classify data access as either legitimate or suspicious, thus streamlining the audit process [23], [24].…”
Section: B Ai/ml In Enhancing Healthcare Privacymentioning
confidence: 99%
“…Finally, PET can be attached to each policy rule. To this end, we evaluated a variety of privacy filters for specific types of data (e.g., location data, health data, or audio data) [222]. These reflect the privacy requirements expressed by data producers.…”
Section: Data Provisioningmentioning
confidence: 99%
“…As more and more personal data are involved, the processing of such data inevitably raises privacy concerns. Therefore, Stach et al [6] investigate which privacy-enhancing technologies (PETs) can be used to systematically conceal certain information patterns contained in the data without compromising the overall data utility. However, in a highly heterogeneous landscape like the IoT, there is no compelling one-size-fits-all solution to this end.…”
Section: Articlesmentioning
confidence: 99%